Legal Problems Concerning Military Disciplinary Punishment - Krittsuansombat, Rapeepong; Chaithongkham, Surathin (Mahachula Academic Journal, 2024)
This thesis has four objectives: (1) to study the concepts, theories, and principles related to military disciplinary punishment; (2) to examine legal measures regarding military discipline in foreign countries in comparison with Thailand; (3) to study and analyze legal issues concerning military punishment in Thailand and abroad; and (4) to propose legal approaches for amending military disciplinary punishment. This research investigates the concepts, theories, and principles related to military disciplinary punishment according to the Military Discipline Act B.E. 2476, utilizing documents and relevant laws from both Thailand and foreign countries. It also examines legal measures related to military discipline in foreign nations compared to those in Thailand, analyzes the legal issues pertaining to military disciplinary punishment in Thailand, and provides recommendations for resolving legal problems concerning military disciplinary measures under the Military Discipline Act B.E. 2476. The study reveals that the law governing military disciplinary punishment is the Military Discipline Act B.E. 2476, which has been in force for a long time without substantial amendments, except for adding some military positions in the Act. This has led to four main problems: (1) the lack of definitions of some specific terms used in the Act and there is no clear boundaries of the law’s application; (2) the absence of legal measures defining the rights and duties of individuals involved in the military disciplinary process and absence of legal measures preserving their rights; (3) the inability to bring disciplinary proceedings to military court; and (4) the lack of legal measures to contest or appeal disciplinary orders issued by superiors to military court, making it difficult to review the discretion exercised in disciplinary decisions. These issues affect the fairness in military disciplinary process. Therefore, the author recommends amending the Military Discipline Act B.E. 2476 and the Military Court Act B.E. 2498 by including definitions for specific terms to clarify the scope and application of the law, adding the duties of commanders and the rights of the accused, and establishing timeframes for the disciplinary process. Furthermore, legal measures should be updated to allow disciplinary cases to be determined by military court and to allow individuals to contest or appeal disciplinary orders. It also suggests Thailand to adopt legal concepts and measures from foreign countries, such as, those of the United States and those of the Federal Republic of Germany to solve the problems in the military disciplinary process in Thailand.